Characterization of the entrepreneurial profile of students belonging to the Business Development course at UNALM - Antonio Vargas, Javier Rubén (2021)
The ability to identify market opportunities, design solutions and build organizational systems are requirements that university students should integrate into their basic training to promote entrepreneurship. In this sense, the purpose of this research was to characterize the students of the Universidad Nacional Agraria La Molina (UNALM) enrolled in the Business Development course in the academic cycles of the years 2018 and 2019 for groups A*, B* and C*. The characterization refers to various aspects related to entrepreneurship, such as the preference for work autonomy, the preference for the type of entrepreneurship, the ability to face problems through entrepreneurship, and the self-perception of entrepreneurial training at the university level. The entrepreneurial profile of the students was analyzed descriptively based on the results of the applied instrument and hypotheses of the relationship between variables were proposed after applying the Top Two Box methodology for the cases that required it. The hypotheses were contrasted using the statistical tests Fisher’s Test and Chi-Square; resulting in: there is a relationship between the gender variable and the preference for incorporating members who seek to be efficient when forming work groups; there is a weak relationship between training to perform specific functions and the preference for including expert people in the work group, there is also a weak relationship between the intention to undertake and training to lead. These findings are important to improve the design of courses related to entrepreneurship and suggest that it is necessary to continue investigating the way in which the variables that characterize entrepreneurial activity interact.